Morphotectonics of mass movements on slopes - Scheidegger, Adrian E. (Journal of Nepal Geological Society, 2000)
The study describes the neotectonic effects on morphology of mass movements. Whilst the external (meteorological or seismic) processes are the immediate triggers of mass movements, their location and orientation is pre-designed by the tectonics of the area. The direction of mass movement is naturally in the direction down the slope of the valleys. If the latter are natural, they are parallel to the prevailing joints, which are shearing features of the neotectonic stress field. Most landslides, thus, are "shear" - or "wedge"-type failures. However, this is not true in the case of older valleys having been cause d e.g. by nappe-edges emplaced much before the present-day resulting in "mountain fractures" and "valley closures", and particularly by artificial cuts: in such cases, slides occur mainly on faces oriented at right angles to one of the principal neotectonic stress directions. Evidently, the stability of the object is reduced in this case and slides occur more frequently than if the valleys or cuts run parallel to such principal stress directions. These findings are illustrated by specific examples from the Himalaya and the Alps.